Metabolic syndrome increases the risk for premature employment exit: A longitudinal study among 60 427 middle-aged and older workers from the Lifelines Cohort Study and Biobank - Katharina Runge; Sander KR van Zon; Kène Henkens; Ute Bültmann (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVES: This study aimed to examine whether (i) metabolic syndrome (MetS) increases the risk for premature employment exit and (ii) a dose-response relationship exists between an increasing number of MetS components and premature employment exit among middle-aged and older workers.METHODS: A sample of N=60 427 Dutch workers (40-64 years old) from the Lifelines Cohort Study and Biobank were examined using data from five measurement waves during a total median follow-up time of 4.2 years. MetS components were based on physical measures, blood markers, and medication use. Premature employment exit types (ie, unemployment, work disability, and early retirement) were determined using questionnaires. MetS and number of MetS components were examined as risk factors for premature employment exit using competing risk regression analysis.RESULTS: MetS significantly increased the risk for work disability [adjusted sub distribution hazard ratio (SHR) 1.78, 95% confidence interval (CI) 1.54-2.05] and unemployment (adjusted SHR 1.16, 95% CI 1.06-1.26). A clear dose-response relationship was found for an increasing number of MetS components and work disability. No associations were found between MetS (components) and early retirement after adjusting for sociodemographic factors.CONCLUSIONS: MetS was identified as a modifiable early-stage cardio-metabolic risk factor especially for work disability and, to a lesser extent, for unemployment. Further, a clear dose-response relationship was found between an increasing number of MetS components and work disability. MetS interventions and prevention might help to prolong working lives. More awareness is needed among employers and occupational health professionals about the premature employment exit risk faced by middle-aged and older workers with MetS.